HLA‐associated antiepileptic drug‐induced cutaneous adverse reactions. (9th April 2019) - Mullan, Kerry A.; Anderson, Alison; Illing, Patricia T.; Kwan, Patrick; Purcell, Anthony W.; Mifsud, Nicole A.
Abstract : Adverse drug reactions (ADRs) are a common cause of hospital admissions (up to 19%), with the majority of cases due to off‐target predictable drug effects (type A reactions). However, idiosyncratic drug‐induced immune activated (type B) reactions contribute to a range of hypersensitivity reactions, with T‐cell‐mediated type IV hypersensitivity reactions mainly manifesting as cutaneous ADRs (cADRs). Aromatic antiepileptic drugs (AEDs), used in the treatment of epilepsy as well as bipolar disorder or neuropathic pain, have been implicated as culprit drugs in a spectrum of pathologies ranging from mild maculopapular exanthema (MPE) to severe and life‐threatening conditions including drug reaction with eosinophilia and systemic symptoms (DRESS), Stevens‐Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN). These AED‐induced cADRs are unpredictable based on pharmacological and clinical factors alone, thereby prompting investigations into genomic contributors mediating risk of pathology. The most strongly associated risk genes identified are from the human leukocyte antigen (HLA) class I alleles, which play a critical role in adaptive immunity by flagging either infected or aberrant cells for recognition by surveying T‐cells. In the setting of drug hypersensitivity, the immunogenicity of HLA molecules and their peptide cargo can be modulated by interactions with small drug molecules that drive inappropriate T‐cell responses. This review discusses the current understanding of HLA class I molecules in modifying risk of AED‐induced cADRs.